1988
DOI: 10.1136/adc.63.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of bronchial hyperreactivity and asthma in relation to environmental factors.

Abstract: SUMMARY A questionnaire study regarding airway morbidity in children and environmental factors was performed in April 1985. The parents of 5301 children, aged 6 months to 16 years, from different rural areas in mid Sweden were sent a validated questionnaire and 4990 (94%) responded. The cumulative prevalence of bronchial hyperreactivity was 9.7% and of allergic asthma 5.2%. Children living near a paper pulp plant more often had symptoms suggesting bronchial hyperreactivity (124 (13.0%), relative risk 1-3) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
1
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(122 citation statements)
references
References 9 publications
7
110
1
4
Order By: Relevance
“…Although it has been suggested that the effects of exposure to damp and to other factors such as environmental tobacco smoke are independent (40), no studies have investigated possible interacting effects of damp or mould with other documented risk factors.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been suggested that the effects of exposure to damp and to other factors such as environmental tobacco smoke are independent (40), no studies have investigated possible interacting effects of damp or mould with other documented risk factors.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…3 shows the odds ratios for cough and wheeze in adults associated with damp and mould in the home (36,(43)(44)(45), and Fig. 4 shows the odds ratios for asthma in both children and adults (33,(39)(40)(41)(43)(44)(45)(46)(47)(48)(49)(50). Approximately half of the studies show a significant association between respiratory symptoms and the presence of damp and mould.…”
Section: Association Between Indoor Damp or Mould Growth And Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this method is convenient and favourable, questionnaire-based methods are difficult to validate against microbial measurements [40,48]. Numerous studies validated self-reported visible mould questions against inspector-reported observations [36,31,[78][79][80][81] and did not find any evidence for over-or underreporting of dampness and mould by occupants. Further, against the backdrop of fungal diversity, it is not clear whether the obviously visible mould or unknown, invisible species contribute to the observed effects in children's health [69,82].…”
Section: Validity Of Exposure Assessmentmentioning
confidence: 99%
“…It is therefore a possibility that indoor pollutants might be of greater importance in the development of asthma than outdoor pollutants. Several studies have shown significant associations between health outcomes and exposure to indoor components like environmental tobacco smoke (12)(13)(14)(15), NO2 (16), mite allergens (17)(18)(19), and mold or dampness (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%